La política comercial de México durante el gobierno del presidente Enrique Peña Nieto - de la Mora Sánchez, Luz María (El Colegio de México A.C., 2019)
The government of President Enrique Peña Nieto maintained an open trade policy and gave a renewed impetus to the trade negotiations agenda with its participation in the Trans-Pacific Partnership Progressive Integration Treaty (TIPAT), the updating of the FTA with the European Union and the initiation of negotiations with some countries in Latin America, Asia and the Middle East. The arrival of President Donald Trump put Mexico’s trade policy in a defensive position. Renegotiating the North American Free Trade Agreement involved paying high costs to maintain preferential access to its main export market.